Determinants of Traditional Contraceptive use among Women - Ike Fitrah Atul Chabibah; Yekti Satriyandari (Women, Midwives and Midwifery, 2022)
Background: Population growth in Indonesia remains high and itconstitutes a population problem which requires the enactment of population policy, namely by reducing the growth rate as low as possible through the family planning programs. 3.8% of women of childbearing age (WCA) in Indonesia still choose to use the traditional family planning methods, including the use of natural ingredients or herbal medicine as the traditional contraception, the use of coitus interruptus method, and the use of calendar method which is lower in effectiveness than modern contraceptive methods. Purpose: The purpose of this study is to review determinants of traditional contraceptive use among women. Methods: Four databases were used to organize this scoping review, namely PubMed, JSTOR, Science Direct, and Google Scholar. These databases wereconsidered to be relevant on condition thatthe scoping review research questions could be answered through the search ofarticles using keywords. To obtain the relevant articles, the inclusion and exclusion criteria were set, then the articles were selected through the PRISMA flow chart. After that, a critical appraisal was conducted to assess the quality of each article, the articles were further condensed using data charting, an evidence-based analysis was compiled, and the results were reported. Results: This study resulted in thefinding of 9 theme-related articles whose research characteristics consisted of grade A for 6 articles, grade B for 1 article, which all employed cross sectional research method, and grade Good for 2 qualitative design articles.These articles were obtained from developing countries. The limitation of this study was that not all factors contained in the collection of articles were discussed by the researchersdue to the lack of comparison journals which matched the theme. Conclusion: The results of scoping review from the titledeterminants of traditional contraceptive use among womenrevealed that there were several related factors including age, education level, economic status, parity, husband’s support, culture and information systems. Based on the 9 articles in this scoping review, the research results on factors related to the use of traditional family planningmethods were supported. However, not all factors such as sexual behavior, smoking, religious prohibitions, health problems and service quality could be studied in depth due to the limited comparison journals. Therefore, the researchers expect that further research can cover all factors related to the use of traditional family planning methods in order to develop knowledge concerning the traditional contraceptive use, and it is expected that the results of this studycanserve the material for government policy making in future family planning programs.